(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This article presents an exhaustive review of these studies and suggests a direction for future developments. This current study shed light on the meaning of mood in Arabic and English Languages. Also, the differences between them and effect of this mood on the linguistic an speech act. This papers have been takled the type of mood in Arabic and English languages.